RADIAL INCREMENT OF OAK AND ASH TREES AS INDICATOR OF FOREST ECOSYSTEMS CONDITION IN NOVOGRAD-VOLYNSKY PHYSIOGRAPHIC REGION - Koval, I. M.; Bologov, О. V.; Nusbaum, S. А.; Juzvinsky, G. А. (Forestry and Forest Melioration, 2018)
Results of dendroclimatic and dendroindicative research of oak and ash stands in Novograd-Volynsky <a href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d1%84%d0%b8%d0%b7%d0%b8%d0%ba%d0%be-%d0%b3%d0%b5%d0%be%d0%b3%d1%80%d0%b0%d1%84%d0%b8%d1%87%d0%b5%d1%81%d0%ba%d0%b8%d0%b9&translation=physiographic&srcLang=ru&destLang=en">physiographic region are presented. Quercus robur L. trees are adapted to change of groundwater level in contrast to Fraxinus excelsior L trees. Dynamic of the tree radial increment confirms this. Increase of groundwater level in places of ash stands growing together with droughts during vegetation period and warm winters have caused tree diseases with root decay and drying ash trees. Drying out of Fraxinus excelsior L. trees occur very quickly. In 2013–2014, up to 90 % of trees were dried out on the sample plot. Increase of temperature, especially during vegetation, early spring and increace of precipitation during cold period are cilimatic factors limiting tree radial increment. Regression model was developed providing a relationship between the oak radial increment and groundwater level.